О строительном деле как показателе развития раннесредневековой Византии - Сорочан, С.Б. (My University, 2004)
S. Sorochan. On Civil Engineering as an Index of Development of Early Mediaeval Byzantium The condition and the degree of specialization of civil engineering of Early Mediaeval Byzantium are evaluated in the article. The author comes to the conclusion that the assertion about the discontinuance of construction in Byzantine cities in «the Dark Ages» is not correct and is unduly exaggerated by some researchers. Even if the certain decrease in building activity was connected with the production of building materials that took place at this time, it was not a significant, universal circumstance and the main thing is that it has not become irreversible.